Corporate social responsibility in Brazilian multinationals - Pinto, Karen Esteves Fernandes (2017)
The purpose of this study is to analyze the relationship between Brazilian multinationals and Corporate Social Responsibility (CSR). The theoretical framework provides relevant information on CSR and on Sustainability-Oriented Innovation (SOI), which are the basis for the development of hypotheses. In order to collect data, an e-survey was conducted with Brazilian multinationals operating in different industries and segments; as result, we obtained 60 valid questionnaires. In order to analyze the data, a multivariate analysis was accomplished, which involved the procedures of canonical correlation and multiple linear regression. The descriptive analysis indicates that most Brazilian multinationals are headquartered in the Southeast region, especially in the State of São Paulo. The outcomes of the multivariate analysis provided empirical support for five hypothesis: there is a positive correlation between the constructs: i) guidelines for multinationals (defined by OECD and emphasized by several scholars) and the compliance with social and environmental regulation; ii) guidelines for multinationals and CSR as differentiation strategy; iii) compliance with social and environmental regulation and CSR as differentiation strategy; iv) SOI practices and guidelines for multinationals; and v) SOI practices and the compliance with social and environmental regulation. The results did not support the hypothesis that predicted a positive correlation between SOI practices and CSR as differentiation strategy.